All eyes on Budak Koleq - Abd Razak, Dzulkifli (2010)
MY alma mater made headlines last week. N. J. Ryan was bestowed the title "Datuk" by the Sultan of Perak. The acclaimed last expatriate headmaster of Malay College Kuala Kangsar (MCKK) wrote a book entitled The Last Expatriate detailing his experience in the institution, better known as "Koleq". He was at the helm from 1959 to 1965, the eighth Mat Salleh after William Hargreaves (to some of us he is "Bargreaves"), who took office in 1905 when the college was established.